2022
DOI: 10.1371/journal.pone.0276798
|View full text |Cite
|
Sign up to set email alerts
|

Modelling bark thickness for Scots pine (Pinus sylvestris L.) and common oak (Quercus robur L.) with recurrent neural networks

Abstract: Variation of the bark depends on tree age, origin, geographic location, or site conditions like temperature and water availability. Most of these variables are characterized by very high variability but above of all are also affected by climate changes. This requires the construction of improved bark thickness models that take this complexity into account. We propose a new approach based on time series. We used a recurrent neural network (ANN) to build the bark thickness model and compare it with stem taper cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…That is, [7] compared the performance of artificial neural networks with non-linear regression models, while [16] compared the performance of the support vector machine for regression with the same technique, in both works the comparisons made with the use of pine and black alder trees bark volume prediction, respectively. [17] used nonlinear autoregressive exogenous neural network technique (recurrent neural network) for estimating the double bark thickness of oak and Scots pine trees. All the above attempts concluded that the machine learning approach has the ability to adequately describe the patterns of the preliminary data in hand.…”
Section: Introductionmentioning
confidence: 99%
“…That is, [7] compared the performance of artificial neural networks with non-linear regression models, while [16] compared the performance of the support vector machine for regression with the same technique, in both works the comparisons made with the use of pine and black alder trees bark volume prediction, respectively. [17] used nonlinear autoregressive exogenous neural network technique (recurrent neural network) for estimating the double bark thickness of oak and Scots pine trees. All the above attempts concluded that the machine learning approach has the ability to adequately describe the patterns of the preliminary data in hand.…”
Section: Introductionmentioning
confidence: 99%